2019
DOI: 10.1101/669390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The thalamic basis of outcome and cognitive impairment in traumatic brain injury

Abstract: Objective: To understand how, biologically, the acute event of traumatic brain injury gives rise to a longterm disease, we address the relationship between evolving cortical and subcortical brain damage and measures of functional outcome and cognitive functioning at six months post-injury.Methods: Longitudinal analysis of clinical and MRI data collected, in a tertiary neurointensive care setting, in a continuous sample of 157 patients surviving moderate to severe traumatic brain injury between 2000 and 2018. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…This is consistent with a subsequent study which found that normobaric hyperoxia may pseudo-normalize the ADC in the cytotoxic rim (Veenith et al, 2014). Acute and early clinical MRI, in conjunction with carefully executed experimental animal studies, can also shed light on the mechanisms underlying msTBI (Lutkenhoff et al, 2019).…”
Section: Conducting International Replication/reproducibility Effort supporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with a subsequent study which found that normobaric hyperoxia may pseudo-normalize the ADC in the cytotoxic rim (Veenith et al, 2014). Acute and early clinical MRI, in conjunction with carefully executed experimental animal studies, can also shed light on the mechanisms underlying msTBI (Lutkenhoff et al, 2019).…”
Section: Conducting International Replication/reproducibility Effort supporting
confidence: 88%
“…However, this information is less valuable for evaluating patients presenting with less severe injuries or more fine-tuned prognostication of long-term neurobehavioral outcome. Indeed, often individuals with similar indicators of severity and early clinical trajectories experience different outcomes (Bigler et al, 2006;Lutkenhoff et al, 2019). Recovery and community reintegration is further complicated by a number of interacting premorbid, clinical, demographic, and genetic factors (Mollayeva et al, 2019).…”
Section: Leveraging Enigma To Address Challenges In Ams-tbi Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a subsequent study which found that normobaric hyperoxia may pseudo-normalize the ADC in the cytotoxic rim (Veenith et al 2014). Acute and early clinical MRI, in conjunction with carefully executed experimental animal studies, can also shed light on the mechanisms underlying msTBI (Lutkenhoff et al 2019). Moreover, the value of early MRI is not limited to structural scans.…”
Section: Standardization Of Image Analysis Protocols For Ams-tbisupporting
confidence: 87%
“…However, this information is less valuable for evaluating patients presenting with less severe injuries or more fine-tuned prognostication of long-term neurobehavioral outcome. Indeed, often individuals with similar indicators of severity and early clinical trajectories experience different outcomes (Bigler et al 2006;Lutkenhoff et al 2019). Recovery and community re-integration are further complicated by a number of interacting premorbid, clinical, demographic, and genetic factors (Mollayeva et al 2019).…”
mentioning
confidence: 99%